2006
DOI: 10.1007/s00127-006-0096-5
|View full text |Cite
|
Sign up to set email alerts
|

Culture shock and social support

Abstract: Social support is an important factor associated with the degree of culture shock and should be taken into consideration in order to protect against or help to overcome this kind of psychological distress experienced by migrants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 19 publications
1
18
1
1
Order By: Relevance
“…The issues regarding the safety of socialising off campus were a concern only to the female respondents which supports previous research regarding the gender and sociocultural adjustment (Fritz et al 2008;Pantelidou and Craig 2006). Female participants consistently reported more distress than the men, particularly regarding the intensity of unwanted attention they received.…”
Section: Social Issuessupporting
confidence: 83%
See 2 more Smart Citations
“…The issues regarding the safety of socialising off campus were a concern only to the female respondents which supports previous research regarding the gender and sociocultural adjustment (Fritz et al 2008;Pantelidou and Craig 2006). Female participants consistently reported more distress than the men, particularly regarding the intensity of unwanted attention they received.…”
Section: Social Issuessupporting
confidence: 83%
“…As with many other research examples, Asians reported more problems with language whereas Europeans experienced more problems in regard to homesickness. Further studies by Pantelidou and Craig (2006) concluded that social support is highly correlated with adjustment as is gender. An analysis of international student retention reveals that men are more likely to experience sociocultural adjustment, as are the extroverted (Fritz et al 2008;Pantelidou and Craig 2006).…”
Section: Sociocultural Adjustmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Bochner's stages then might look like those outlined in . If an acculturalisation process is seen to take place in stages (Adler, 1975; Bochner, 1982; Pantelidou & Craig, 2006) then perhaps those in (G1) and (G2) are further along this process. They travel this journey of integration as they move through counselling training, into practice and assimilate knowledge and understanding from the psychological world.…”
Section: Discussionmentioning
confidence: 99%
“…Transition between cultures is often a difficult process, but it is through that process higher levels of integration emerge (Matsumoto, Hiryama, & LeRoux 2006). There are a number of models that describe this process (Adler, 1975; Bochner, 1982; Pantelidou, & Craig, 2006; Zapf, 1991), and counsellors need an ability to develop appropriate interventions. In certain instances it may be appropriate to add more specific competencies when working with particular client groups (Collins & Arthur, 2010).…”
Section: Introductionmentioning
confidence: 99%